The effects on cognitive behavioural therapy and yoga on stress - Balakrishnan Parasuraman; Muhammad Madi Abdullah; Aryana Satrya; Balakrishnan Muniapan (2009)
This study compares a stress management program based on cognitive behavioural therapy principles with yoga-based stress management program. A study sample of 30 student. The subject were divided into 3 equal groups.